A PROPERLY EVEN HARMONIOUS LABELING OF SOME WHEEL GRAPH W_n FOR n IS EVEN - Nisa, Fakhrun; Fathoni, M. Ivan Ariful; Brata, Adika Setia (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
A properly even harmonious labeling of a graph G with q edges is an injective mapping f from the vertices of graph G to the integers from 0 to 2q-1 such that induces a bijective mapping f* from the edges of G to {0,2,...,2q-2} defined by f*(v_iv_j)=(f(v_i)+f(v_j))(mod2q). A graph that has a properly even harmonious labeling is called a properly even harmonious graph. In this research, we will show the existence of a properly even harmonious labeling of some wheel graph W_n for n is even.